Social workers’ family resources and their readiness to change - Czechowska-Bieluga, Marta (EDUsfera. Ewa Jurczyk-Romanowska, 2020)
This article discusses the correlations between social worker’s family resources and their readiness to change. Preliminary definition of the understanding of the analysed categories and the role those categories play in the performance of social work with a family have provided the basis for the analysis of own research results.
Keywords: readiness to change; social worker; family resources